Rol de la justicia indígena Ecuatoriana en los casos de extorsión en la Parroquia Toacaso - Torres Silva, Marilin Mishel (2024)
Indigenous justice has been a fundamental part of the life of indigenous communities since colonial times, based on customary law and ancestral traditions. In Ecuador, its importance and recognition have been reflected in the 2008 Constitution, especially in Article 171, which guarantees the jurisdictional functions of indigenous authorities to resolve internal conflicts according to their own rules and procedures, being crucial to understand how indigenous communities deal with crimes such as extortion within their jurisdiction. The objective of this research is to analyze the application of indigenous justice in extortion cases in the Toacaso parish, in order to understand the role it plays in the resolution of these cases. For this purpose, a qualitative methodology was used, employing descriptive, documentary or bibliographic research and field research. Data collection was carried out through interviews with indigenous authorities of the Toacaso parish and experts in the field. The results of these interviews revealed that indigenous justice focuses on reintegration and community harmony, using sanctions ranging from public apologies to economic compensation and symbolic physical punishment, in the same way they will act in extortion crimes even though this crime has not been known and resolved by the indigenous authorities before. In conclusion, indigenous justice has mechanisms to resolve any type of crime, but murder is not part of these mechanisms. In the case of the lynching of two alleged extortionists in the community of Plancha Loma, Toacaso parish, the indigenous authorities did not intervene in the lynching, so this fact cannot be attributed to indigenous justice since this justice system must guarantee the protection of human rights enshrined in the Magna Carta and international instruments